Taxing interacting externalities of ocean acidification, global warming, and eutrophication. (18th June 2021) - Hänsel, Martin C.; van den Bergh, Jeroen C. J. M.
Abstract: We model a stylized economy dependent on agriculture and fisheries to study optimal environmental policy in the face of interacting external effects of ocean acidification, global warming, and eutrophication. This allows us to capture some of the latest insights from research on ocean acidification. Using a static two‐sector general equilibrium model we derive optimal rules for national taxes on CO 2 emissions and agricultural run‐off and show how they depend on both isolated and interacting damage effects. In addition, we derive a second‐best rule for a tax on agricultural run‐off of fertilizers for the realistic case that effective internalization of CO 2 externalities is lacking. The results contribute to a better understanding of the social costs of ocean acidification in coastal economies when there is interaction with other environmental stressors. Recommendations for Resource Managers: Marginal environmental damages from CO 2 emissions should be internalized by a tax on CO 2 emissions that is high enough to not only reflect marginal damages from temperature increases, but also marginal damages from ocean acidification and the interaction of both with regional sources of acidification like nutrient run‐off from agriculture. In the absence of serious national policies that fully internalize externalities, a sufficiently high tax on regional nutrient run‐off of fertilizers used in agricultural production can limit not only marginal environmental damages from nutrient run‐off but also account for unregulated carbon emissions. Putting such regional policies in place that consider multiple important drivers of environmental change will be of particular importance for developing coastal economies that are likely to suffer the most from ocean acidification.